Perancangan Sign System Kawasan Wisata Yussar Fishing and Playground Sidoarjo - Athika Dwi Wiji Utami; Putra Uji Deva Satrio; Sonhaji Arif; Masnuna; Muchlisiniyati Safeyah; Sri Wulandari; Aninditya Daniar (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
Yussar Fishing and Playground Sidoarjo is an educational tour in Kalidawir Village, Tanggulangin District, Sidoarjo Regency. Yussar Fishing and Playground Sidoarjo provide rides for fishing ponds, playgrounds, photo spots, education, culinary tours, performing arts, and natural scenery in the form of fish ponds. As a tourist place, Yussar Fishing and Playground Sidoarjo should be able to provide security and comfort for its visitors, especially the Yussar Fishing and Playground Sidoarjo environment is surrounded by fish ponds, so visitors must be more careful in traveling activities at Yussar Fishing and Playground Sidoarjo. The location of Yussar Fishing and Playground Sidoarjo which is in remote villages can make it difficult for people to know its existence, so in this case, Yussar Fishing and Playground Sidoarjo requires environmental graphics as information media in the form of a sign system regarding the existence of Yussar Fishing and Playground Sidoarjo, location instructions for Yussar Fishing and Playground Sidoarjo, and information on warnings/bans. The design of this sign system uses research methods that are divided into three parts, namely pre-production, production, and post-production. The icon used in the sign system is taken from the shape of a fish which is the advantage of Yussar Fishing and Playground Sidoarjo which has a fishing pond facility. The sign system as the primary media has 3 types, namely 9 information sign designs, 6 directions sign designs, and 6 prohibition sign designs. Each type of sign system has a difference in the board's shape and the color of the text so that the message's recipient can easily distinguish the information conveyed. All signs are placed outside and around the Yussar Fishing and Playground area of ​​Sidoarjo according to the type and purpose of each sign.